2016
DOI: 10.1002/mnfr.201500890
|View full text |Cite
|
Sign up to set email alerts
|

Purified rutin and rutin‐rich asparagus attenuates disease severity and tissue damage following dextran sodium sulfate‐induced colitis

Abstract: These findings demonstrate that dietary cooked ASP and its flavonoid glycoside, RUT, may be useful in attenuating colitis severity by modulating the colonic microenvironment resulting in reduced colonic inflammation, promotion of colonic mucosal injury repair, and attenuation of colitis-associated microbial dysbiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 96 publications
(154 reference statements)
0
16
0
Order By: Relevance
“…Our results suggested that productions of IL‐6, IL‐12, and TNF‐α were significantly reduced by TEs, whereas productions of IL‐10 were significantly increased by TEs compared to that of DSS group. These findings were similar to the previous studies, which indicated the therapeutic effects of phytochemicals enriched extracts from tea, fruits, as well as the individual phytochemicals involving epigallocatechin gallate, rutin, and free amino acids in colitis mice …”
Section: Resultsmentioning
confidence: 99%
“…Our results suggested that productions of IL‐6, IL‐12, and TNF‐α were significantly reduced by TEs, whereas productions of IL‐10 were significantly increased by TEs compared to that of DSS group. These findings were similar to the previous studies, which indicated the therapeutic effects of phytochemicals enriched extracts from tea, fruits, as well as the individual phytochemicals involving epigallocatechin gallate, rutin, and free amino acids in colitis mice …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the species from Butyricimonas (OTU 61092, OTU22852, and OTU43831), S24-7 (OTU52622, OTU52789, OTU67103, OTU4618, and OTU11187), Oscillospira (OTU9917), Clostridiales (OTU60609 and OTU71112), and Bilophila (OTU2261) were significantly increased by ethanol diet and markedly reversed by astaxanthin supplementation. It has been reported that the abundance of Oscillospira and Clostridales increased in inflammatory response and is associated with the barrier injury of intestinal mucosa [ 48 , 49 ]. Stanislawski et al demonstrated that Bilophila was positively correlated with the fat fraction of the liver [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary factors might also modulate Rac1 activity, and consequently might strengthen intestinal barrier activity under physiological conditions or alleviate inflammatory severity and mucosal restitution following resolution of inflammation. In this context, Rutin-rich asparagus and black beans attenuate DSS-induced colitis by modulating the colonic microbiota, resulting in improved barrier integrity and upregulation of effectors of injury repair, including Rac1 [78,79].…”
Section: Intestinal Barrier Integrity/mucosal Repair/colitismentioning
confidence: 99%